Atlanta robbin'. Season 2 [videorecording (DVD)] - Glover, Donald, 1983-; Glover, Donald, 1983-; Henry, Brian Tyree; Stanfield, LaKeith, 1991-; Beetz, Zazie (20th Century Fox, 2019)
Two cousins work through the Atlanta music scene to better their lives and the lives of their families. Earn Marks is a young manager trying to get his cousin's career off the ground. Alfred is a new hot rapper trying to understand the line between real life and street life. Darius is Alfred's right-hand man and visionary. Van is Earns best friend and the mother of Earn's daughter.